A system for simulating the kinematics and measuring the impact force from riding whips used in thoroughbred horseracing - Bridge, J. W.; Dempsey, K. M.; Danicki, K. M.; Angotti, R. L.; Kwiatkowski, A. K.; Heleski, C. R.; Peterson, M. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
Thirty horse racing whips of four different designs were tested to measure dynamic impact force and compared using a specially designed mechanical testing device to simulate the whipping action of a jockey during racing. The whips tested included designs used in Thoroughbred horse racing in North America, which meet the design criteria established by the Association of Racing Commissioners International (ARCI) model rules, as well as the most common whip used in British horse racing. The objective of the device was to allow comparisons to be made between peak impact loads resulting from different whip designs. A high peak dynamic force on a horse`s shoulder or hind quarter may result in injuries, such as welts. The testing device contains a planar three-bar, open mechanical linkage loaded by torsion springs to model the arm motion of a jockey. The whip strikes a flat plate covered by an elastomeric pad. The energy input is replicated during the simulated impact. A single axis dynamic load cell under the loading plate and three single-turn precision potentiometers located at each joint of the three-arm mechanical system measure impact forces and relative angular positions, respectively. Force measurements are compared from the face of each whip and the edge or seam where applicable. In addition to the flap design, other physical differences between whip designs included mass, shaft length, shaft stiffness, flap cushion thickness/compression factor, flap surface area, and flap seam area. Statistically significant impact force differences were found between flap face and flap seam impact orientations, with higher impact forces delivered by the flap face. Significant differences were also found in impact forces between the three whip styles with seams.